Cambridge checkpoint lower secondary science grade 7 - Riley, Peter D. (London: Hodder education, 2023)
The Cambridge Checkpoint Lower Secondary Science Grade 7 introduces intermediate concepts in biology, chemistry, and physics. It emphasizes critical thinking, inquiry-based learning, and real-world application. Topics include ecosystems, chemical reactions, and energy transfer, fostering scientific understanding and skills development through engaging content and practical activities.
Keywords: Science